Study on the Fracture Evolution Law of Coal Based on Image Retrieval Method and X-Ray Computed Tomography. (4th March 2022) - Wu, Yan; Wang, Dengke; Pang, Xiaofei; Zhang, Hang
Abstract : The combination of real-time computed tomography (CT) scanning test and loading test can visualize the evolution process of defects such as internal pores and fissures in the coal. The axial deformation of the loaded coal sample will change the layers of the same section in the real-time CT scanning test, which will affect the analysis of fracture progression. To address the concern, we presented a CT image similarity retrieval method. The dynamic development law of fracture networks under triaxial stress was investigated using image processing technologies. The results reveal that the CT images of the coal sample in the same section can be obtained using the proposed CT image similarity retrieval method, which can more accurately characterize the fracture distribution and dynamic evolution law. The coal sample under triaxial stress experienced three fracture evolution stages: the closure in the compaction and elastic stages, the initiation and development in the plastic yield stage, and the rapid expansion and penetration in the postpeak stage. The variation trend of two-dimensional fracture ratio and fracture volume was consistent. The analysis is conducive to clarifying the coal failure mechanism under triaxial stress.